Optimizing mesh size of gill nets to capture the skipjack tuna, Katsuwonus pelamis (Linnaeus) in Thoothukkudi, south east coast of India - Neethiselvan, N; Jude, D (Indian Journal of Fisheries, 2011)
<!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> Katsuwonus pelamis, a coastal tuna popularly called â€˜skipjackâ€™ form a commercial fishery in Thoothukkudi coast from June to September in gill nets with mesh size ranging from 60 to 135mm. The fishery is mainly constituted by length group ranging from 325 to 725 mm. The study deals with optimization of mesh size to capture the commercially significant size group (451-600mm) which contributed about 77.4% of the annual tuna landings of Thoothukkudi during the year 1999. The optimum mesh size for commercial exploitation of K. pelamis in Thoothukkudi is estimated as 125 mm. Gill net with 125 mm mesh size would capture length groups which have crossed length at first maturity and hence would pave way for the sustained fishery of K. pelamis in this coast